(untitled) (Sains Humanika, 2019)
Road safety awareness is a important element subject in which also involved school students. The school students are the most prone group of that become the victims of the road accidents. This study is carried out to identify the road safety awareness, knowledge, driving attitudes among secondary school students in Parit Raja, Johor. The study was involved a total of 298 school students as respondents. The questionnaires were distributed and the data were processed using descriptive statistics, t-test, correlation and regression analyses. The descriptive analysis shows, more than half of respondents are those aged 16 years old. About 76.5% of them do not have the driving license. The result also shows that the road safety awareness among the students is at quite high level (mean score = 3.57). Next, t-test and regression analysis shows that every 1% increase in road safety awareness will affect 35.0% of increase to driving attitude among students (p<0.05, Î² = 0.35). Besides that, the factor analysis, items in the variable of Road Safety Factor shows that there are three methods of road safety are identified; Environment of Highway, Uses of Highway and Law of Road Safety. Therefore, road safety awareness and driving attitudes are the important factors to ensure the road user concern to road safety. However, some improvements to the existing road facility or road safety deficiencies in Parit Raja need to be undertaken to ensure the road is safer to others.